2012
DOI: 10.1038/nrneph.2012.92
|View full text |Cite
|
Sign up to set email alerts
|

Klotho as a potential biomarker and therapy for acute kidney injury

Abstract: Klotho is a single-pass transmembrane protein that is highly expressed in the kidney and is known to act as a coreceptor for fibroblast growth factor 23. The extracellular domain can be produced independently or shed from membrane-bound Klotho and functions as an endocrine substance with multiple functions including antioxidation, modulation of ion transport, suppression of fibrosis, and preservation of stem cells. Emerging evidence has revealed that Klotho deficiency is an early event in acute kidney injury (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
127
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(133 citation statements)
references
References 72 publications
5
127
0
1
Order By: Relevance
“…16) Emerging experimental and clinical evidence indicates that during the progression of AKI from diverse etiologies, sklotho decreases significantly in the early phase. [17][18][19] Also, gene expression studies in AKI have clearly demonstrated rapid and significant down regulation of KL mRNA in the thick ascending limb of Henle's loop and the collecting ducts, with resultant decreased synthesis of klotho protein and secretion into the circulation. 20,21) CIN, as a distinct subtype of AKI, might share a similar kidney damage process.…”
Section: Discussionmentioning
confidence: 99%
“…16) Emerging experimental and clinical evidence indicates that during the progression of AKI from diverse etiologies, sklotho decreases significantly in the early phase. [17][18][19] Also, gene expression studies in AKI have clearly demonstrated rapid and significant down regulation of KL mRNA in the thick ascending limb of Henle's loop and the collecting ducts, with resultant decreased synthesis of klotho protein and secretion into the circulation. 20,21) CIN, as a distinct subtype of AKI, might share a similar kidney damage process.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is derived from either cleavage of Klotho from the cell membrane or alternative splicing. Several renoprotective (18)(19)(20) and vasculoprotective (21,22) effects have been ascribed to sKlotho. With the recent establishment of an ELISA (23), sKlotho may become another CKD-MBD biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…5 TNF superfamily inflammatory cytokines, TGF-b1 or angiotensin II, decrease Klotho expression in cultured tubular cells. 2,3,7,8 Zhou et al 4 confirm a TNFindependent Klotho-lowering effect of TGF-b1 in cultured renal cells. Zhou et al 4 propose that TGF-b1 could be the culprit behind Klotho depletion in diseased kidneys.…”
mentioning
confidence: 99%
“…A key function of Klotho is to regulate phosphate metabolism by both being a necessary coreceptor for the phosphaturic hormone fibroblast growth factor-23 and directly inhibiting tubular phosphate reabsorption by the sodium-phosphate cotransporter NaPi2a. 2,3 In addition, a growing list of actions of soluble Klotho depend on its glycosidase activity or binding to cell membrane receptors and transporters and as reported by Zhou et al, 2,4 soluble ligands. Thus, Klotho regulates insulin/IGF-1, Wnt, and TGF-b1 signaling as well as renal outer medullary potassium channel (ROMK), transient receptor potential channel 5 (TRPC5), and TRPC6 availability.…”
mentioning
confidence: 99%
See 1 more Smart Citation